A patient with solid gynecologic cancer causing lactic acidosis, severe hypercalcemia, and hypoglycemia. Issue 1 (12th November 2018) - Hausken, John; Haave, Ellen M.; Haugaa, Håkon; Løberg, Else M.; Kongsgaard, Ulf E.
Key Clinical Message: Though rare in cervical cancer patients, paraneoplastic syndrome usually presents with several endocrine and hormonal symptoms. Knowledge of the pathophysiology that underlies these abnormalities is beneficial to diagnosis and treatment. An interdisciplinary approach and test analysis prior to initiating specific treatment is recommended, though prognosis appears poor in advanced cases. Abstract : Though rare in cervical cancer patients, paraneoplastic syndrome usually presents with several endocrine and hormonal symptoms. Knowledge of the pathophysiology that underlies these abnormalities is beneficial to diagnosis and treatment. An interdisciplinary approach and test analysis prior to initiating specific treatment is recommended, though prognosis appears poor in advanced cases.